Serum Amyloid A1 Induces Classically Activated Macrophages: A Role for Enhanced Fibril Formation - Gaiser, Ann-Kathrin; Bauer, Shanna; Ruez, Stephanie; Holzmann, Karlheinz; Fändrich, Marcus; Syrovets, Tatiana; Simmet, Thomas (Frontiers in Immunology, 2021)
AA amyloidosis belongs to the group of amyloid diseases which can follow chronic inflammatory conditions of various origin. The disease is characterized by the deposition of insoluble amyloid fibrils formed by serum amyloid A1 (SAA1) leading eventually to organ failure. Macrophages are intimately involved in the fibrillogenesis as well as in the clearance of amyloid fibrils. In vivo, macrophages may occur as classically (M1) or alternatively activated (M2) macrophages. We investigate here how SAA1 might affect the macrophage polarization and function. Gene microarray analysis revealed upregulation of 64 M1-associated genes by SAA1. M1-like polarization was further confirmed by the expression of the M1-marker MARCO, activation of the NF-κB transcription factor, and secretion of the M1-cytokines TNF-α, IL-6, and MCP-1. Additionally, we demonstrate here that M1-like polarized macrophages exhibit enhanced fibrillogenic activity towards SAA1. Based on our data, we propose reconsideration of the currently used cellular amyloidosis models towards an in vitro model employing M1-like polarized macrophages. Furthermore, the data suggest macrophage repolarization as potential intervention strategy in AA amyloidosis.